Analisis Pengendalian Kualitas Produk Paving Block Menggunakan Metode Statistical Quality Control (SQC) Dan Failure Mode Effect Analysis (FMEA) Di PT. Duta Beton Mandiri, Pasuruan - Mochammad Fathan Yuda Haryono; Sumiati Sumiati (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
PT. Duta Beton Mandiri is a company that is part of DUTA BANGSA GROUP domiciled in the Pasuruan regency. PT. Duta Beton Mandiri is a manufacturing company that has been established since 2008 and engaged in the production of building materials or concrete industry which has products such as paving blocks, bricks, ready mix, and precast concrete. PT. Duta Beton Mandiri is still often faced with several defects in their production, especially in paving block products as one of their main products such as easily crushed paving, cracked paving, asymmetrical paving, non-dry/wet paving and also damaged paving which affects quality. The purpose of this study was to determine the presentation of the most dominant defects, the factors causing the defects, and the effects they caused, as well as to propose the appropriate improvements to improve the quality of paving block products. The methods used are Statistical Quality Control (SQC) and Failure Mode and Effect Analysis (FMEA). SQC tools are check sheets, stratification, histograms, paretto diagrams, scatter diagrams, control charts, and cause and effect diagrams. Meanwhile, FMEA is used as a proposal to improve the results of the cause-and-effect diagram. Based on the results of research on SQC, the most dominant defects were Easily crushed paving (38,34%), after that Cracked paving (28,86%), Damaged paving (13,83%), Asymmetrical paving (10,92) and Non-dry/wet paving (8,05%). Based on the results of analysis and calculations on FMEA, it is known that the problem causing disability with the highest RPN value of 384 is the machine factor with the cause of the paving block mold pallet in a dirty or worn position. Recommendations for improvements that can be made are by always checking the condition of the mold pallet before the production process starts on a regular basis.